2021
DOI: 10.1155/2021/8042755
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Study of Virtual Reality Augmented Technology Combined with Contrast-Enhanced Ultrasound in the Assessment of Thyroid Cancer

Abstract: Thyroid cancer has become the most common malignant tumor in the endocrine system, and its global incidence has been showing an upward trend. The diagnosis methods of thyroid cancer include ultrasound, fine-needle aspiration cytology, and neck CT, but the single ultrasound feature cannot simultaneously take into account the sensitivity and specificity of more than 85% when diagnosing thyroid cancer. The development of virtual technology can significantly improve the diagnosis of the thyroid gland. Based on thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It’s possible that CEUS allows for an increased visualization of the thyroid nodule which improves the accuracy of the ablation and further improves the safety of ablation treatment, and reduces the occurrence of complications. 24 , 25 Based on the above analysis, when treating BTNs clinically, we suggest that those who meet the following conditions can actively choose CEUS-guided RFA to further improve the clinical benefits of patients: Patients whose nodules are benign, who have no prior history of radiation therapy, who have autonomic functional nodules, hyperthyroidism symptoms, or conscious symptoms. At the same time, attention should be paid to the elimination of contraindications of RFA treatment which are as below: Patients with huge retrosternal goiter, or nodules located retrosternal, vocal cord insufficiency contralateral to the lesion, coagulation impairment, or organ insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…It’s possible that CEUS allows for an increased visualization of the thyroid nodule which improves the accuracy of the ablation and further improves the safety of ablation treatment, and reduces the occurrence of complications. 24 , 25 Based on the above analysis, when treating BTNs clinically, we suggest that those who meet the following conditions can actively choose CEUS-guided RFA to further improve the clinical benefits of patients: Patients whose nodules are benign, who have no prior history of radiation therapy, who have autonomic functional nodules, hyperthyroidism symptoms, or conscious symptoms. At the same time, attention should be paid to the elimination of contraindications of RFA treatment which are as below: Patients with huge retrosternal goiter, or nodules located retrosternal, vocal cord insufficiency contralateral to the lesion, coagulation impairment, or organ insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%